Interactive sonification of motion: Design, implementation and control of expressive auditory feedback with mobile devices - Dubus, G. (Trita-CSC-A, 2013)
Sound and motion are intrinsically related, by their physical nature and through the link between auditory perception and motor control. If sound provides information about the characteristics of a movement, a movement can also be influenced or triggered by a sound pattern. This thesis investigates how this link can be reinforced by means of interactive sonification. Sonification, the use of sound to communicate, perceptualize and interpret data, can be used in many different contexts. It is particularly well suited for time-related tasks such as monitoring and synchronization, and is therefore an ideal candidate to support the design of applications related to physical training. Our objectives are to develop and investigate computational models for the sonification of motion data with a particular focus on expressive movement and gesture, and for the sonification of elite athletes movements. We chose to develop our applications on a mobile platform in order to make use of advanced interaction modes using an easily accessible technology. In addition, networking capabilities of modern smartphones potentially allow for adding a social dimension to our sonification applications by extending them to several collaborating users. The sport of rowing was chosen to illustrate the assistance that an interactive sonification system can provide to elite athletes. Bringing into play complex interactions between various kinematic and kinetic quantities, studies on rowing kinematics provide guidelines to optimize rowing efficiency, e.g. by minimizing velocity fluctuations around average velocity. However, rowers can only rely on sparse cues to get information relative to boat velocity, such as the sound made by the water splashing on the hull. We believe that an interactive augmented feedback communicating the dynamic evolution of some kinematic quantities could represent a promising way of enhancing the training of elite rowers. Since only limited space is available on a rowing boat, the use of mobile phones appears appropriate for handling streams of incoming data from various sensors and generating an auditory feedback simultaneously. The development of sonification models for rowing and their design evaluation in offline conditions are presented in Paper I. In Paper II, three different models for sonifying the synchronization of the movements of two users holding a mobile phone are explored. Sonification of expressive gestures by means of expressive music performance is tackled in Paper III. In Paper IV, we introduce a database of mobile applications related to sound and music computing. An overview of the field of sonification is presented in Paper V, along with a systematic review of mapping strategies for sonifying physical quantities. Physical and auditory dimensions were both classified into generic conceptual dimensions, and proportion of use was analyzed in order to identify the most popular mappings. Finally, Paper VI summarizes experiments conducted with the Swedish national rowing team in order to assess sonification models in an interactive context. Content: 1: Evaluation of four models for the sonification of elite rowing 2: Interactive sonification of synchronisation of motoric behaviour in social active listening to music with mobile devices 3: Interactive sonification of expressive hand gestures on a handheld device 4: An overview of sound and music applications for Android available on the market 5: A systematic review of mapping strategies for the sonification of physical quantities 6: Evaluation of a system for the sonification of elite rowing in an interactive context